2012
DOI: 10.3109/17453674.2012.718518
|View full text |Cite
|
Sign up to set email alerts
|

Use of porous trabecular metal augments with impaction bone grafting in management of acetabular bone loss

Abstract: Background The use of impaction grafting in revisions with larger acetabular bone defects has mixed outcomes and sometimes high failures rates.Patients and methods This prospective, single-center study involved a consecutive series of 24 patients who underwent complex reconstruction of the acetabulum using a trabecular metal augment, impaction bone grafting, and a cemented high-density polyethylene cup. Patients were followed for median 5 (3–7) years.Results The 2-year WOMAC pain, function, and stiffness score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 32 publications
1
54
0
2
Order By: Relevance
“…Metal augments try to create peripheral acetabular containment to facilitate graft impaction [16]. Different series have been recently published reporting good preliminary results [3,13,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Metal augments try to create peripheral acetabular containment to facilitate graft impaction [16]. Different series have been recently published reporting good preliminary results [3,13,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Iwase et al showed that acetabular IBG reconstruction was indicated in cases in which the maximum acetabular defect distance was within 20 mm and the problem was a simple wall defect [12]. They suggested using a reinforcement ring or a cage with bulk allograft [13] [14] or porous trabecular metal auguments [6] [7] with IBG for cases with >20 mm maximum acetabular defect distance combined with multiple segmental wall defects [12]. Van Haaren et al…”
Section: Discussionmentioning
confidence: 99%
“…A combination of these methods may also be considered. The use of morselized cancellous bone graft and a cementless porous coated acetabular component is also a well-established acetabular revision surgical technique in the presence of bone deficiency [6] [7]. These options are often inadequate, however, when the acetabular bone loss is great.…”
Section: Introductionmentioning
confidence: 99%
“…3 Possible options for management of these defects include jumbosized cups, cup-cage constructs, and trabecular metal augments. [3][4][5] Unfortunately, studies have shown revision…”
Section: Introductionmentioning
confidence: 99%